Corporate Governance Practice in Indonesia - Doddy Setiawan (Jurnal Akuntansi dan Bisnis, 2007)
This article aims at analyzing the corporate governance practice in Indonesia. One of reason financial crisis happened in Indonesia is poor corporate governance (La Porta et. al, 2000; Johnson, et.al, 2000; Dyck, 2000; Husnan, 2000). Corporate governance is how to govern the firms. One of important characteristic Indonesian law is Indonesia using two-tier of board systems. Indonesian firms have boards of director and board of commissioner. Johnson et al. (2000), La Porta et al. (2000a,b), Husnan (2000), Tabalujan (2000) argues that poor corporate governance in the form of poor law enforcement as one factors that causing the financial crisis. Johnson et al. (2000) believes that weak law institution lead to depreciation and stock market decline in East Asia. The weak legal institution and poor law enforcement allowing large shareholder/managers expropriate minority shareholder. If the expropriation by managers increase because their stock falling, it will lead to low capital inflow and high capital outflow. These it will lead to decrease stock price and depreciation of currency exchange. Therefore Indonesia suffered from financial crisis.